Practices and experiences of incarceration : an inquiry into Papéis da Prisão by José Luandino Vieira - Scaraggi, Elisa (2021)
Considered one of the fathers of Angolan literature and one among the most important contemporary writers in Portuguese, in 1961 José Luandino Vieira was arrested because of his participation to the struggle for independence in Angola. He would spend the next twelve years in confinement, first in Luanda and later in the notorious Tarrafal prison camp (Cabo Verde). While in detention, Vieira wrote most of his literary works, alongside a series of notebooks in which he reported his thoughts, feelings and literary and political considerations. Forty years after the independence of Angola, Vieira’s notebooks were published in a volume titled Papéis da prisão: Apontamentos, diário, correspondência (1962-1971). In this dissertation, I focus on the intersections between history, literature and the writing of the self that can be observed in Vieira’s prison writings. I defend that, while the prison diaries cast a new light on the writer’s literary production, they can also bring new elements to the history of Angola, having an impact on how the history of the struggle will be remembered in the future. Starting from a reflection on the issue of punishment and on prison as an instrument of social control, I question how the writings related to their locale of production, how the carceral experience had shaped them and how it was reflected in them.